Perlakuan Akuntansi Aset Tetap pada Kantor Kecamatan Siluq Ngurai Kabupaten Kutai Barat - Simson Gabend (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
ABSTRAK                 Samson. 2017. Accounting treatment of fixed assets at the Siluq Ngurai District Office of Kutai Barat Regency. (under guidance lecturer supervisor I Levi Malisan and and lecturer II Indra Suyoto Kurniawan).               The purpose of this research is to know the treatment of fixed asset at Siluq Ngurai District Office of West Kutai Regency. The study used quantitative analysis.Based on the results of the research analysis, it can be concluded as follows: The treatment of fixed assets in the form of land has not complied with Statement of Government Accounting Standard (PSAP) Number 07 Year 2010 pursuant to Government Regulation Number 71 Year 2010. This is due to unsuitable assessment, presentation and disclosure. For example the land where the District Office of Siluq Ngurai in Muhur Village granted by the citizens in 2005 with the value of own estimate of Rp 345,000,000. Presentation of data on December 30, 2016 remains written for Rp 345,000,000 (fixed value / license plate). The book value of 2016 should be adjusted to the taxable book value (NJOP) of the fiscal year 2016. The treatment of fixed assets in the form of equipment and machinery has not complied with Statement of Government Accounting Standards (PSAP) Number 07 Year 2010 pursuant to Government Regulation Number 71 Year 2010 due to the assessment, inappropriate presentation and disclosure. This is because there is no calculation of economic age, depreciation and inclusion of current value. For example a Honda motorcycle type Win type purchased (procurement) in 2002 is still written worth the purchase of Rp 6,000,000. If the calculated residual value based on the economic life of the motorcycle is 7 years, then the goods should have entered the item being scrapped or auctioned to the community / local employee. The treatment of fixed assets in the form of buildings and buildings has not complied with Statement of Government Accounting Standard (PSAP) Number 07 Year 2010 pursuant to Government Regulation Number 71 Year 2010 due to unsuitable assessment, presentation and disclosure. This is because there is no calculation of economic / technical life usage, depreciation and inclusion of present value. For example, fixed assets are Muhur Kampung Pertemuan Umum (BPU) buildings, no year of construction / delivery, no usage / technical life, depreciation value and present value / book value. The value is still listed the value of procurement / development amounting to Rp 117.600.000. Similarly for other fixed assets in the form of buildings and buildings, they do not include depreciation and present value. The treatment of fixed assets in the form of roads, bridges and irrigation has not complied with Statement of Government Accounting Standards (PSAP) Number 07 Year 2010 in accordance with Government Regulation Number 71 Year 2010 due to unsuitable measurement, assessment, presentation and disclosure. This is because there is no volume calculation (length and width), economic / technical life age, depreciation and inclusion of present value. For example, fixed assets consist of special roads to the Siluq Ngurai Sub-district Office that was built in 2010, not included volumes, no usage life / technical age, did not calculate depreciation value and present value / book value. The value is still included value of procurement / development Rp 224.060.000 (value of 2010). Similarly for other fixed assets land for road plans, other special roads and power grids to the Siluq Ngurai District office, all of which do not include volume, depreciation and present value                                    Keywords: Fixed Assets, Siluq Ngurai, Accounting Treatment